Strengthening Health Services in Low Income Countries : Guidance for Decision-Makers - Øvretveit, John (World Bank, Washington, DC, 2017)
Health systems in lower income countries are often not able to provide for the basichealth needs of their populations. The progress of recent initiatives such as the WHO millennium development goals and new funds for disease programs is slowed by the limitations of these health service and systems. Strengthening these health systems has become a priority, but this cannot be achieved immediately, the causes of these limitations are many, complex and with deep historical origins. It is important to ensure that the new resources are used in ways which effectively strengthen these services and systems in both the short and long term. There is some experience and research which has found effective ways to strengthen service delivery and system functioning. However, this research is largely unknown or unused by policy makers and decision makers in ministries, local government, aid agencies and work bank advisors. Although evidence from elsewhere will need to be adapted to the local situation, this research can help avoid expensive mistakes and save time and money in choosing and implementing effective health service strengthening strategies. The purpose of this report is to present some of the first guidance and materials from the world bank ‘improving health service program’ (WB IHSP). It gives interim guidance based on the best available evidence which was identified in a rapid review of actions for strengthening health services and systems.